Efektivitas Implementasi Program Mahasiswa Wirausaha (PMW) Terintegrasi Pembelajaran MBKM untuk Meningkatkan Keterampilan Berwirausaha Mahasiswa Universitas Jambi - Arpizal Arpizal; Nurmala Sari; Novia Sri Dwijayanti; Ahmad Nasori; Iwan Putra (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Based on results from the IDN Research Institute in 2019, 69.1% of millennials in Indonesia have an interest in entrepreneurship. The interest and entrepreneurial potential of this great millennial generation needs to be supported and facilitated through higher education governance that supports student entrepreneurship programs in universities. Thus, the existence of the Student Entrepreneurial Program (PMW) in Higher Education is very important to be implemented and developed. The purpose of this study was to determine the effectiveness of the implementation of the Student Entrepreneurial Program (PMW) at Jambi University through the integration of Independent Learning-Independent Campus learning to improve the entrepreneurial skills of Jambi University students in 2021. This study used a survey method, with an expost de facto approach. The sampling technique used in this study is probability sampling with a total sample of 206 respondents from a total population of 426 PMW participating students at Jambi University in 2021. From the results of the study it was found that students of the Jambi University Student Entrepreneurial Program (PMW) in 2021 perceived that PMW which is measured based on the PMW objective indicator has been effectively implemented with a score of 3.29 in the very high category. Entrepreneurship skills are measured based on three skill indicators, namely personal skills, interpersonal skills, and process skills, with a student perception score of 3.38, 3.31 and 3.27 in very high category, respectively. Thus, it can be concluded that the implementation of the Student Entrepreneurial Program is effective in improving the entrepreneurial skills of Jambi University students in 2021.